MOTIVASI PENDAMPING TERHADAP KELOMPOK TANI DI DESA KINUNANG KECAMATAN LIKUPANG TIMUR KABUPATEN MINAHASA UTARA - Ema ., Rumbrawer; Leonardus R. Rengkung; Jenny ., Baroleh (AGRI-SOSIOEKONOMI, 2017)
This study aims to determine the companion motivation of farmer groups in the village of Kinunang, District Likupang East, North Minahasa District. This study was conducted from May to July 2017. The data used were primary data obtained from each farmer group through direct interviews with 30 (thirty) respondents using questionnaires that were asked to the heads of farmer groups in Kinunang Village in East Likupang Sub-district. Secondary data is obtained directly from books, and articles. The data obtained will be analyzed using descriptive analysis which each answer is tested and tested using Likert scale. The results of this study indicate that the motivation of farmer group supporters is very important in the empowerment of farmer groups both at the level of beginner and advanced in the activity.